2009
DOI: 10.2196/jmir.1100
|View full text |Cite
|
Sign up to set email alerts
|

A Text Message–Based Intervention for Weight Loss: Randomized Controlled Trial

Abstract: BackgroundTo our knowledge, no studies have evaluated whether weight loss can be promoted in overweight adults through the use of an intervention that is largely based on daily SMS (Short Message Service: text) and MMS (Multimedia Message Service: small picture) messages transmitted via mobile phones.Objective This paper describes the development and evaluation of a text message–based intervention designed to help individuals lose or maintain weight over 4 months.Methods The study was a randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
593
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(617 citation statements)
references
References 27 publications
18
593
2
4
Order By: Relevance
“…There was a noted reduction in binge drinking following the use of the app (Carrà et al, 2016), and the findings of this study provide further support for the acceptability of mobile technology, as a response rate of 82% was achieved, with 98% of participants reporting that the eHealth app was easy to use (Carrà et al, 2015). A wealth of evidence demonstrates that electronic communication based interventions are widely accepted by both young people (Britto et al, 2012;Dennison et al, 2013;Lim et al, 2012) and a number of other population groups (Arora et al, 2012;Patrick et al, 2009;Proudfoot et al, 2010). This would indicate that the high acceptability rate of mobile technologies may result in a higher engagement, as supported by the findings in this review.…”
Section: Discussionsupporting
confidence: 65%
“…There was a noted reduction in binge drinking following the use of the app (Carrà et al, 2016), and the findings of this study provide further support for the acceptability of mobile technology, as a response rate of 82% was achieved, with 98% of participants reporting that the eHealth app was easy to use (Carrà et al, 2015). A wealth of evidence demonstrates that electronic communication based interventions are widely accepted by both young people (Britto et al, 2012;Dennison et al, 2013;Lim et al, 2012) and a number of other population groups (Arora et al, 2012;Patrick et al, 2009;Proudfoot et al, 2010). This would indicate that the high acceptability rate of mobile technologies may result in a higher engagement, as supported by the findings in this review.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, another finding from the stratified analyses was that the Web-based programs did not have a significant additional weight-loss effect unless their use was combined with face-to-face support. These results suggest that an in-person contact 29 Instruction, self-monitoring and counseling Counseling, self-monitoring or only material Maintenance Cussler et al 30 Instruction, self-monitoring and counseling Self-directed Maintenance Hunter et al 31 Instruction, self-monitoring and counseling Counseling via phone Self-help Loss Digenio et al 32 Counseling Material Material with counseling (via phone or face-to-face) or only material Loss Patrick et al 18 Instruction Counseling Material Loss van Wier et al 19 Instruction and counseling Material Material Loss Morgan et al 33 Instruction and self-monitoring Material Loss Ueki et al 34 Instruction and self-monitoring Instruction via fax/mail and supplemental food (jelly) Effect of lifestyle modification on weight control S Kodama et al approach is superior to a technology-based approach from the viewpoint of the amount of weight loss; if used, an Internet program needs to include the component of a faceto-face program for participants to achieve weight loss. It is known that social support is one of the important aspects of behavioral obesity treatment and is associated with better weight-loss outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Table 2 shows details of the obesity treatment programs in each included study. To summarize the study-specific Webbased programs in terms of the role of the Internet, 16 studies [18][19][20][23][24][26][27][28][30][31][33][34][35][36][38][39] used the Internet as an adjunct to the non-Web-based obesity care support provided in both control and experimental groups. One study 25 used it as a substitute for face-to-face counseling.…”
Section: Data Synthesismentioning
confidence: 99%
“…However, several studies have demonstrated that text messaging for weight loss on regular mobile phones (feature phones) is feasible and effective. For example, one recent study found that a research-designed mobile phone intervention providing automated and interactive text messages with personalized feedback was more effective at inducing short-term weight loss than print-based self-help materials [40]. The growing evidence for the efficacy of text messaging implies that until we have evidence on what is effective with smartphone apps, smartphone apps should be designed to include proactive and interactive text messages as a feature of the app.…”
Section: Discussionmentioning
confidence: 99%